Optimalisasi Program CSR Dreamwork PT Pertamina Patra Niaga FT Bandung dalam Pemberdayaan Anak Disabilitas - Arinda Putri Wulandari; Sahadi Humaedi; Santoso Tri Raharjo (GUYUB: Journal of Community Engagement, 2025)
Children with disabilities often face significant barriers in accessing education, skills training, and economic opportunities, compounded by limited support from their immediate environment. Proper mentoring and needs-based vocational training are essential to foster their confidence and independence. This community service initiative aims to empower children with disabilities through vocational training and family mentoring in the Dreamwork Program initiated by PT Pertamina Patra Niaga FT Bandung. Using the AIR method (Activity, Input, Result) and the Pentahelix collaboration model—which involves academics, businesses, communities, government, and media—the program systematically integrates stakeholders in the empowerment process. As a result, participants demonstrated measurable improvements, including the ability to produce marketable products such as handicrafts and processed food, with some families successfully marketing their products through local community bazaars and online platforms. Additionally, family members became more actively involved, with 80% participating in mentoring sessions and business development discussions. The program also succeeded in establishing three new collaboration networks with local business actors and media outlets, contributing to increased public awareness regarding the importance of social inclusion for persons with disabilities.